Geochemical exploration in calcrete terrains - Krug, Mark Alan (Rhodes University, Faculty of Science, Department of Geology, 1995)
This work takes a look at some of the literature on calcretes and especially the problem of geochemical exploration in calcrete terrains. The conclusion that will be reached is that exploration in calcrete terrains is not futile and that provided the explorationist is aware of the types of calcrete and their genetic implications calcrete can be used as a sampling medium and anomalies can be detected through calcrete (p.1.),KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Duricrusts; Silcrete; Geochemical prospecting